TURKU TAKING STEPS TOWARDS FUTURE - technology supports physical activity - Serene, Ritesh (My University, 2011)
Physical activity (PA) is an important field of healthcare research internationally and within Finland. As technology devices and services penetrate deeper levels within society, the need for studying the usefulness for PA turns vital. We started this research work by reviewing literature consisting of two hundred research journals, all of which have found technology to significantly improve an individual’s ability to get motivation and achieve officially recommended levels of physical activity, like the 10000 steps a day, being tracked with the help of pedometers. Physical activity recommendations require sustained encouragement, consistent performance in order to achieve the long term benefits. We surveyed within the city of Turku, how the motivation levels and thirty three other criterions encompassing technology awareness, adoption and usage attitudes are impacted. Our aim was to know the factors responsible for achieving consistent growth in activity levels within the individuals and focus groups, as well as to determine the causes of failures and for collecting user experience feedback. The survey results were quite interesting and contain impeccable information for this field. While the focus groups confirmed the theory established by past studies within our literature review, it also establishes our research propositions that ict tools and services have provided and can further add higher benefits and value to individuals in tracking and maintain their activity levels consistently for longer time durations. This thesis includes two new models which dictate technology and physical activity adoption patterns based on four easy to evaluate criterions, thereby helping the healthcare providers to recommend improvements and address issues with an easy rule based approach. This research work provides vital clues on technology based healthcare objectives and achievement of standard PA recommendations by people within Turku and nearby regions.